Effect of Continuous Posttraumatic Intrathecal Nocistatin on the Development of Mechanical Allodynia. Issue 1 (1st January 2011) - Hermanns, Henning; Muth-Selbach, Uta; Krug, Sabrina; Williams, Ruth; Braun, Sebastian; Werdehausen, Robert; Schlösser, Lukas; Bauer, Inge
Abstract : Background and Objectives: The neuropeptide nocistatin has a variety of effects on nociception and other central nervous system functions. It has shown to exert diverging effects on nociceptive behavior in various experimental pain models depending on the dose administered. The inhibitory effect of spinal nocistatin on the release of glycine and γ-aminobutyric acid is thought to be responsible for pronociceptive effects, whereas the antinociceptive action of nocistatin can be attributed to diminished glycine-dependent N -methyl-d-aspartate receptor activation. So far, nocistatin has only been investigated in experimental models of already established pain and has been injected as a bolus. Methods: In the present study, we investigated the effects of continuous intrathecal administration of nocistatin on the development of mechanical allodynia in the chronic constriction injury model of neuropathic pain in rats. The spinal infusion via intrathecal catheters connected to osmotic minipumps was started immediately after the surgical procedure and lasted 24 hrs. The development of mechanical allodynia was assessed with von Frey-type filaments for 2 weeks after chronic constriction injury. Results: Despite a wide range of doses used, the continuous spinal application of nocistatin had no significant effect on the development of pathological nociceptive behavior at any time point, that is, mechanical allodynia developed equally in all groups in the injured paw, whereas nociceptive behavior was unchanged in comparison with baseline values in the uninjured paw in all groups. Conclusions: Because nocistatin has well-documented effects on established pathological pain, it is conceivable that its effect on nociception is only effective when spinal circuitry is pathologically altered.